Ice rafted debris and reconstructed sea surface temperature of ODP Hole 104-642B - Paul E Bachem; Bjørg Risebrobakken; Erin L McClymont (PANGAEA, 2016)
The mid-Piacenzian warm period (3.264-3.025 Ma) of the Pliocene epoch has been proposed as a possible reference for future warm climate states. However, there is significant disagreement over the magnitude of high latitude warming between data and models for this period of time, raising questions about the driving mechanisms and responsible feedbacks. We have developed a new set of orbital-resolution alkenone-based sea surface temperature (SST) and ice rafted debris (IRD) records from the Norwegian Sea spanning 3.264-3.14 Ma. The SSTs in the Norwegian Sea were 2-3 °C warmer than the Holocene average, likely caused by the radiative effect of higher atmospheric CO2 concentrations. There is notable obliquity-driven SST variability with a range of 4 °C, shown by evolutive spectra. The correlation of SST variability with the presence of IRD suggests a common climate forcing acting across the Nordic Seas region. Changes of the SST gradient between the Norwegian Sea and North Atlantic sites suggest that the subpolar gyre was at least as strong as during the Holocene, and that the northward heat transport by the North Atlantic Current was comparable.
Supplement to: Bachem, PE et al. (2016): Sea surface temperature variability in the Norwegian Sea during the late Pliocene linked to subpolar gyre strength and radiative forcing. Earth and Planetary Science Letters, 446, 113-122, https://doi.org/10.1016/j.epsl.2016.04.024